2012
DOI: 10.5194/hess-16-2085-2012
|View full text |Cite
|
Sign up to set email alerts
|

Soil property changes over a 120-yr chronosequence from forest to agriculture in western Kenya

Abstract: Abstract. Much of the native forest in the highlands of western Kenya has been converted to agricultural land in order to feed the growing population, and more land is being cleared. In tropical Africa, this land use change results in progressive soil degradation, as the period of cultivation increases. Both rates and variation in infiltration, soil carbon concentration and other soil parameters are influenced by management within agricultural systems, but they have rarely been well documented in East Africa. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 71 publications
9
33
0
Order By: Relevance
“…The increase in bulk density with intensification of land use was mirrored by a decrease in the water infiltration capacity. This observation concurs with the findings of Nyberg et al (2012) who found that conversion of natural forest to agricultural land uses can lead to reductions of 60% in the infiltration rate within 40 years after conversion in western Kenya. Results from our study showed higher median infiltration rates compared to results by Nyberg et al (2012), who did their experiments only 70 km away from our study sites.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in bulk density with intensification of land use was mirrored by a decrease in the water infiltration capacity. This observation concurs with the findings of Nyberg et al (2012) who found that conversion of natural forest to agricultural land uses can lead to reductions of 60% in the infiltration rate within 40 years after conversion in western Kenya. Results from our study showed higher median infiltration rates compared to results by Nyberg et al (2012), who did their experiments only 70 km away from our study sites.…”
Section: Discussionsupporting
confidence: 92%
“…However, the time that would be needed for a complete recovery will vary greatly across different landscapes and ecosystems-a major determinant being past land use and land management. Several studies have investigated the effects of land cover type and land use history on soil hydraulic properties (e.g., infiltrability and Ksat; Bonell et al, 2010;Descheemaeker et al, 2006;Elsenbeer, Newton, Dunne, & de Moraes, 1999;Lal, 1996;Niemeyer, Fremier, Heinse, Chávez, & DeClerck, 2014;Nyberg et al, 2012;Yimer, Messing, Ledin, & Abdelkadir, 2008;Zimmermann, Elsenbeer, & De Moraes, 2006). However, fewer studies have looked explicitly at forest age to understand the recovery of these properties under secondary succession (see examples listed in Table 1), and to our knowledge, no studies of this kind were carried out in dry tropical forests.…”
mentioning
confidence: 99%
“…Conversely, Price et al (2010) showed that the hydraulic properties decreased after a forest was converted to a non-forest because soil compaction associated with land management practices. Moreover, Nyberg et al (2012) reported that soil infiltrability decreased with time after a forest was converted to a cropland, with decreased in soil carbon and nitrogen and increased soil bulk density.…”
mentioning
confidence: 99%